2020
DOI: 10.1080/09658211.2020.1749283
|View full text |Cite
|
Sign up to set email alerts
|

Fewer generation constraints increase the generation effect for item and source memory through enhanced relational processing

Abstract: Memory is often better for information that is self-generated versus read (i.e., the generation effect). Theoretical work attributes the generation effect to two mechanisms: enhanced itemspecific and relational processing (i.e., the two-factor theory). Recent work has demonstrated that the generation effect increases when generation tasks place lower, relative to higher, constraints on what participants can self-generate. This study examined whether the effects of generation constraint on memory might be attri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

7
1

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 62 publications
(168 reference statements)
4
15
0
Order By: Relevance
“…Altogether, these findings suggest that details that pertain to planning for the future, such as one’s future survival, are prioritized in memory, which may have been shaped in our evolutionary past. Finding ways to improve memory is an important pursuit ( Rogers et al, 1977 ; Butler and Roediger, 2007 ; Leshikar et al, 2012 , 2017 ; Matzen et al, 2015 ; Leach et al, 2018 ; McCurdy et al, 2020 ), and this work contributes to a wider body of research investigating how memory might be enhanced.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Altogether, these findings suggest that details that pertain to planning for the future, such as one’s future survival, are prioritized in memory, which may have been shaped in our evolutionary past. Finding ways to improve memory is an important pursuit ( Rogers et al, 1977 ; Butler and Roediger, 2007 ; Leshikar et al, 2012 , 2017 ; Matzen et al, 2015 ; Leach et al, 2018 ; McCurdy et al, 2020 ), and this work contributes to a wider body of research investigating how memory might be enhanced.…”
Section: Discussionmentioning
confidence: 97%
“…Our color context finding provides some evidence in line with this idea. Although some of the past work on enhanced relational processing has focused on how survival processing enhances memory across trials (for example, across lists of items that are related), work in another memory domain (generation effect) has shown that enhanced relational processing leads to increased performance for context memory ( Marsh et al, 2001 ; McCurdy et al, 2017 , 2019 , 2020 ). Thus, in the present data, it may be that survival processing induced enhanced relational processing between the item and its color that was especially pronounced for the plausibly colored items under survival processing conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the existing generation effect theories do not differentiate across generation tasks (all generation tasks are typically viewed as equivalent), but recent work strongly challenges this idea. Research shows that the magnitude of the generation effect is influenced by certain features of the task used, such as generation constraint (McCurdy, McCurdy, Sklenar, Frankenstein, & Leshikar, 2020), which refers to the amount of information given to the participant that limits, or constrains, what can be produced in a generation task. For example, in a standard generation procedure, participants are often given one or multiple constraints, such as a generation rule (e.g., "generate a synonym"), a cue word from which to generate a target, and letter(s) of the target word (e.g., "reply-an____").…”
mentioning
confidence: 99%
“…These constraints serve to ensure that the participant produces the expected target response to reduce itemselection confounds (i.e., idiosyncratic or unique generated responses). Some work, however, shows that tasks placing fewer constraints on what participants can generate increases the memory benefits for self-generated materials compared with tasks with more constraints (Fiedler, Lachnit, Fay, & Krug, 1992;Gardiner, Smith, Richardson, Burrows, & Williams, 1985;McCurdy et al, 2020). Given that generation effect studies use tasks that involve varying amounts of constraints (some higher, some lower), it is possible to evaluate the history of work on the generation effect to probe this factor.…”
mentioning
confidence: 99%
“…Third, participants were asked “When you saw this word before, was it in upper case or lower case?” (v = upper case | b = lower case | m = DK) which served as our case context memory judgment. The “do not know” response option was included to minimize potential data contamination by guesses as done before ( Duarte et al, 2008 ; Leshikar et al, 2015 ; McCurdy et al, 2017 , 2019 , 2020 ). All responses were made with the index, middle, ring, and pinky finger of the right hand.…”
Section: Methodsmentioning
confidence: 99%